2020
DOI: 10.47466/hikmah.v15i2.137
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kemampuan Menghafal Al-Qur'an dan Sikap Siswa Terhadap Hasil Belajar Matematika

Abstract: The purpose of this study is to determine the effect of ability to memorize al-Qur'an, students' attitude, and interactions both of them towards students' learning outcomes in mathematics. The research method used is the correlational survey method, the number of sample are 60 students from two classes who conduct memorization of Al-Qur'an. Data collection was done by using questionnaire distribution and test technique. Data analysis using correlation analysis and mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
1
3
0
3
Order By: Relevance
“…This is in line with Khotimah's research result. It shows that memorizing the Qur'an affects the level of mathematics learning outcomes on Madrasah Ibtidaiyah students (Khotimah, 2020). This is indicated by the significant difference between the mathematics learning outcomes of students who memorize the Qur'an and the students who do not memorize the Qur'an.…”
Section: Introductionmentioning
confidence: 94%
“…This is in line with Khotimah's research result. It shows that memorizing the Qur'an affects the level of mathematics learning outcomes on Madrasah Ibtidaiyah students (Khotimah, 2020). This is indicated by the significant difference between the mathematics learning outcomes of students who memorize the Qur'an and the students who do not memorize the Qur'an.…”
Section: Introductionmentioning
confidence: 94%
“…Konsentrasi merupakan induk dari semua aktifitas pembelajaran, namun ironisnya sangat banyak siswa yang tidak atau belum mampu berkonsentrasi. Ketidak beradaan pihak yang mampu mengajari mereka terkait dengan konsentrasi, baik guru maupun orang tua, turut menyebabkan hal ini (Khotimah, 2020).…”
Section: Pendahuluanunclassified
“…Pada penelitian ini, Khoiriyah (2021) menemukan hubungan yang signifikan secara bersama-sama antara kemampuan menghafal Al-Qur'an dan Habits of Mind dengan penguasaan konsep materi sistem pernapasan pada peserta didik. Selanjutnya dari penelitian Sita Husnul Khotimah yang membahas mengenai Pengaruh Kemampuan Menghafal Al-Qur'an Dan Sikap Siswa Terhadap Hasil Belajar Matematika (Khotimah, 2020). Tujuan dari penelitian tersebut adalah untuk mengetahui pengaruh kemampuan menghafal al-Qur'an, sikap siswa dan interaksi keduanya terhadap hasil belajar matematika siswa.…”
Section: Pembahasanunclassified
“…Many researches have raised the theme of the correlation between memorizing the Quran and students' achievement and learning outcomes in mathematics. From some of these studies, it was found that memorizing the Quran can affect learning achievement, learning outcomes, and emotional intelligence (Khotimah, 2020;Neni, 2015;Romi et al, 2018). Some of the researches above have similarities in one variable, namely memorizing the Koran.…”
Section: Introductionmentioning
confidence: 99%